2016
DOI: 10.2196/mental.5597
|View full text |Cite
|
Sign up to set email alerts
|

Can We Foster a Culture of Peer Support and Promote Mental Health in Adolescence Using a Web-Based App? A Control Group Study

Abstract: BackgroundAdolescence with its many transitions is a vulnerable period for the development of mental illnesses. Establishing effective mental health promotion programs for this age group is a challenge crucial to societal health. Programs must account for the specific developmental tasks that adolescents face. Considering peer influence and fostering adolescent autonomy strivings is essential. Participation in a program should be compelling to young people, and their affinity to new technologies offers unprece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…From these, 12 studies were ultimately included [ 30 - 41 ]. Reasons for exclusion included not being a research paper [ 42 ], not being qualitative or having a qualitative component [ 43 - 50 ], investigating the wrong phenomena of interest [ 51 - 53 ], not meeting the definition of mHealth [ 54 , 55 ], the population being outside the target age band [ 19 , 56 - 62 ], and the population being affected by a condition not considered to be a chronic NCD (eg, mHealth promotion interventions with no specific chronic NCD or lifestyle behaviors) [ 63 - 66 ]. Seven studies contributed findings on end users [ 30 , 31 , 33 - 35 , 37 , 39 ], whereas 5 studies [ 32 , 36 , 38 , 40 , 41 ] reported on implementers.…”
Section: Resultsmentioning
confidence: 99%
“…From these, 12 studies were ultimately included [ 30 - 41 ]. Reasons for exclusion included not being a research paper [ 42 ], not being qualitative or having a qualitative component [ 43 - 50 ], investigating the wrong phenomena of interest [ 51 - 53 ], not meeting the definition of mHealth [ 54 , 55 ], the population being outside the target age band [ 19 , 56 - 62 ], and the population being affected by a condition not considered to be a chronic NCD (eg, mHealth promotion interventions with no specific chronic NCD or lifestyle behaviors) [ 63 - 66 ]. Seven studies contributed findings on end users [ 30 , 31 , 33 - 35 , 37 , 39 ], whereas 5 studies [ 32 , 36 , 38 , 40 , 41 ] reported on implementers.…”
Section: Resultsmentioning
confidence: 99%
“…Previous trials of mental health apps with young people highlight the difficulties in achieving program adherence within this population (37). Despite minimal feedback on ways to improve the app at the conclusion of Study One, the incorporation of elements to improve engagement and completion rates are required, highlighted by the links between completion and symptom change highlighted in Study Two.…”
Section: Discussionmentioning
confidence: 99%
“…Including social support in the form of peer mentors can be additionally included in the process to increase participation. Peer mentors can give advice or support healthy behavior with small incentives [ 84 ]. Including an incentive system to increase participation in eHealth programs could be a success factor for increasing participation as well [ 59 , 72 ].…”
Section: Implementation Of Ehealth Tools In Workplace Health Promotiomentioning
confidence: 99%